2021
DOI: 10.1111/tbed.14313
|View full text |Cite
|
Sign up to set email alerts
|

Geo‐clusters and socio‐demographic profiles at village‐level associated with COVID‐19 incidence in the metropolitan city of Jakarta: An ecological study

Abstract: The Special Capital Region of Jakarta is the epicentre of the transmission of COVID‐19 in Indonesia. However, much remains unknown about the spatial and temporal patterns of COVID‐19 incidence and related socio‐demographic factors explaining the variations of COVID‐19 incidence at local level. COVID‐19 cases at the village level of Jakarta from March 2020 to June 2021 were analyzed from the local public COVID‐19 dashboard. Global and local spatial clustering of COVID‐19 incidence was examined using the Moran's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Many studies on the spatial aspects of the Covid-19 case have been carried out around the world (Ballesteros et al, 2021;Edriani et al, 2021;Hu et al, 2021;Lak et al, 2021;Mohammad Ebrahimi et al, 2021;Pang et al, 2021;Purwanto et al, 2021;Raymundo et al, 2021;Saavedra et al, 2021). Not much has been done to study the spatial aspects of the Indonesian Covid-19 case (Dhewantara et al, 2022;Heldayani et al, 2021;Iriany et al, 2021;Ratnasari & Dewi, 2021). Spatial distribution analysis using the Getis Ord G* method is a technique that is often and widely used, one of which is the detection of hotspots or disease clusters (ESRI, 2021;Hohl et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies on the spatial aspects of the Covid-19 case have been carried out around the world (Ballesteros et al, 2021;Edriani et al, 2021;Hu et al, 2021;Lak et al, 2021;Mohammad Ebrahimi et al, 2021;Pang et al, 2021;Purwanto et al, 2021;Raymundo et al, 2021;Saavedra et al, 2021). Not much has been done to study the spatial aspects of the Indonesian Covid-19 case (Dhewantara et al, 2022;Heldayani et al, 2021;Iriany et al, 2021;Ratnasari & Dewi, 2021). Spatial distribution analysis using the Getis Ord G* method is a technique that is often and widely used, one of which is the detection of hotspots or disease clusters (ESRI, 2021;Hohl et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In Germany, most research on the spatial distribution of COVID-19 is restricted to the relatively coarse level of counties [16], masking important variation at the small-area, municipality, or even neighbourhood level, hampering productive outbreak detection and management, despite numerous studies' having shown the value of microgeographic data on COVID-19 [17][18][19].…”
Section: Introductionmentioning
confidence: 99%